The well-being of women at work: the importance of resources across the life course. Issue 4 (8th July 2014) - Carla C.J.M. Millar and Dr Vicki Culpin, Professor; L. Gervais, Roxane; Millear, Prudence
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the factors that impact on the well-being of women workers, as assessed through depression, anxiety and stress, across the life course, i.e. age, marital status and parental status. Design/methodology/approach – The quantitative study was cross-sectional in nature and used an online self-report questionnaire to generate information on job/work characteristics, belief systems and demographic variables. A snowball sample was used to recruit the respondents. Findings – The results showed that the availability of resources was the influencing factor in women workers maintaining their well-being. Those respondents with resources, such as job autonomy and support from colleagues, were less likely to be depressed, anxious or stressed. The life course was not an influencing factor in the models tested suggesting that regardless of women's stage in life, they require appropriate resources to address the demands of the work environment, to maintain their well-being. Practical implications – The implications of this study are that when considering diversity in the work environment, it is important to assess if all workers have the resources they require to cope with the demands of the workplace. Originality/value – This present study outlines the importance of the life course in the context of the workplace, but highlights also that it is only one perspective and that others should be considered; such as those factors that are inherent in improving well-being and relationships within organisations.